Analysis and evaluation of food spending patterns for the residents of Jablah - صقر ابراهيم; مسلم رنيم (Latakia University Journal -Biological Sciences Series, 2021)
The aim of the research is to identify the reality of food expenditure for Syrian families, in the city of Jableh, and the impact of the global war that afflicted Syria during the period 2011-2020 on that reality. Using Richard Geiger’s law, the size of the studied sample was 380 families, randomly selected from 16 different neighborhoods of the city. The descriptive approach was used to describe the economic and social status of the studied sample, and the analytical approach was used to study the relationship between the economic and social characteristics of the studied sample and the amount of food consumed. The results of the research showed that the average monthly household expenditure on food amounted to about 123,984 SP, during the period 2019-2020, where spending on vegetables occupied the largest percentage (17.4%) of the total expenditure on food, followed by all kinds of meat (11.9%), sugar and tea. and coffee (11.8%), then cereals (11.2%). The results also showed that 76.6% of the total sample studied were completely affected by the current crisis, 58.7% of them depend on other sources of income. The research recommends the necessity of moving towards vertical expansion in agriculture, and increasing the monthly income of the Syrian individual in proportion to the current prices of food commodities.